Genetic Risk Scores Implicated in Adult Bone Fragility Associate With Pediatric Bone Density. (14th December 2015) - Mitchell, Jonathan A; Chesi, Alessandra; Elci, Okan; McCormack, Shana E; Roy, Sani M; Kalkwarf, Heidi J; Lappe, Joan M; Gilsanz, Vicente; Oberfield, Sharon E; Shepherd, John A; Kelly, Andrea; Grant, Struan FA; et al.
ABSTRACT: Using adult identified bone mineral density (BMD) loci, we calculated genetic risk scores (GRS) to determine if they were associated with changes in BMD during childhood. Longitudinal data from the Bone Mineral Density in Childhood Study were analyzed ( N  = 798, 54% female, all European ancestry). Participants had up to 6 annual dual energy X‐ray scans, from which areal BMD (aBMD) Z ‐scores for the spine, total hip, and femoral neck were estimated, as well as total body less head bone mineral content (TBLH‐BMC) Z ‐scores. Sixty‐three single‐nucleotide polymorphisms (SNPs) were genotyped, and the percentage of BMD‐lowering alleles carried was calculated (overall adult GRS). Subtype GRS that include SNPs associated with fracture risk, pediatric BMD, WNT signaling, RANK‐RANKL‐OPG, and mesenchymal stem cell differentiation were also calculated. Linear mixed effects models were used to test associations between each GRS and bone Z ‐scores, and if any association differed by sex and/or chronological age. The overall adult, fracture, and WNT signaling GRS were associated with lower Z ‐scores (eg, spine aBMD Z ‐score: βadult  = –0.04, p  = 3.4 × 10 −7 ; βfracture  = –0.02, p  = 8.9 × 10 −6 ; βWNT  = –0.01, p  = 3.9 × 10 −4 ). The overall adult GRS was more strongly associated with lower Z ‐scores in females ( p ‐interaction ≤ 0.05 for all sites). The fracture GRS was more strongly associated with lower Z ‐scores with increasing age ( p ‐interaction ≤ 0.05 for all sites). The WNT GRS associations remained consistent for both sexes and all ages ( p ‐interaction > 0.05 for all sites). The RANK‐RANKL‐OPG GRS was more strongly associated in females with increasing age ( p ‐interaction < 0.05 for all sites). The mesenchymal stem cell GRS was associated with lower total hip and femoral neck Z ‐scores, in both boys and girls, across all ages. No associations were observed between the pediatric GRS and bone Z ‐scores. In conclusion, adult identified BMD loci associated with BMD and BMC in the pediatric setting, especially in females and in loci involved in fracture risk and WNT signaling. © 2015 American Society for Bone and Mineral Research.